The Tendencies of Mathematics' Teaching Staff Members in Saudi Arabia Towards Using "Blackboard" in University Teaching and Their Training Requirements - Al-Mazruei, Safa Ahmed; Al-Awaidi, Afrah Hafez (Journal of Educational and Psychological Sciences, 2021)
The extract This study aims to detect the tendencies of the mathematics teaching staff in Saudi universities towards using the E- learning management system " Blackboard" in learning and university teaching. And it asks for their training requirements and if there are statistically significant differences between the responds of the sample studies individuals among universities teaching staff. It is about using blackboards in teaching Mathematics that could be attributed to gender variable, academic degree as well as their training background. So, for achieving this objective, the researcher has used the descriptive approach and she used " questionnaire" as a studying tool. The study sample is made up of) 73( teaching member staff whom the "questionnaire" has been sent to them Research's results showed that the tendencies' overall average for teaching member staff is positive with (2.66) percentage. Similarly, the study has shown positive results towards the need for more training on the use of the blackboard system. The study identified a set of recommendations; the most significant is related to: scaling up this experience in all Saudi universities. Beside providing the continuous and intensive training for the teaching staff members and students on the use of the E-learning management system " Blackboard".
Keywords: Blackboard; distance education; electronic learning; Mathematics' Teaching Staff Members; Training Requirements